Strukturiranost poznorimske poselitve Slovenije - Ciglenečki, Slavko (Arheološki vestnik, 1997)
The article presents a survey of current knowledge about settlement and colonization in the Late Roman period. The cities and the problem of their abandonment in the 5th century are first discussed, along with the origin of the numerous new or reused elevated sites. A brief survey is offered of the various settlement types, such as military stations, refugii, caves, and especially settlements with walled buildings in the interior. A hiatus in settlement in the 5th century is noted, particulary in its central third. The addendum considers two elements of the Battle at Frigidus. The author examined the supposed blockade on the road bellow Col and established that no evidence for this exists in the field. In terms of the location of the elevated fortified camp of St. Paul above Planina, the archaeological results to the present as well as the description in Theodoretus indicate that Eugenius may have stayed there during the battle.
Keywords: archaeology; arheologija; arheološke najdbe; mesta; poselitev; Slovenia; Slovenija